Insulin resistance modifies the association between obesity and current asthma in adults. Issue 2 (21st April 2016) - Cardet, Juan Carlos; Ash, Samuel; Kusa, Tope; Camargo, Carlos A.; Israel, Elliot
Insulin resistance potentiates the association between obesity and childhood asthma, but this relationship appears inconsistent in relatively small studies of adults. We investigated effect modification in adults using the National Health and Nutrition Examination Survey 2003–2012, a large, nationally representative database. Insulin resistance and a history of physician-diagnosed current asthma were obtained from 12 421 adults, ages 18–85 years. We used logistic regression to determine associations between obesity and current asthma, adjusting for age, sex, race/ethnicity, poverty income ratio and smoking status. An interaction term evaluated effect modification by insulin resistance of the obesity–asthma association. As expected, obesity was positively associated with current asthma. Insulin resistance modified this association, with obesity measured as body mass index, waist circumference or waist-to-height ratio. The relationship between obesity and current asthma was stronger with increasing insulin resistance tertiles (OR 2.05, 95% CI 2.76–3.00; p-value for interaction 0.03). This association was robust to adjustments for other components of the metabolic syndrome (hypertriglyceridaemia, hypertension, hyperglycaemia and systemic inflammation). None of these components were themselves effect modifiers of the obesity–asthma association. In this large, nationally representative sample, insulin resistance modified the association between obesity and current asthma in adults. Targeting insulin resistance may represent a novel therapeutic strategy for obese patients with asthma. Insulin resistance potentiates the obesity–asthma association and may be a therapeutic target in obese asthmatics http://ow.ly/Zu9bb